Pathogenesis and research progress in leukoaraiosis - Sun, Lingqi; Hui, Lin; Li, Yi; Chen, Xian; Liu, Rong; Ma, Ji (Frontiers in Human Neuroscience, 2022)
Leukoaraiosis is a common imaging marker of cerebral small vessel disease. In recent years, with the continuous advances in brain imaging technology, the detection rate of leukoaraiosis is higher and its clinical subtypes are gradually gaining attention. Although leukoaraiosis has long been considered an incidental finding with no therapeutic necessity, there is now growing evidence linking it to, among other things, cognitive impairment and a high risk of death after stroke. Due to different research methods, some of the findings are inconsistent and even contradictory. Therefore, a comprehensive and in-depth study of risk factors for leukoaraiosis is of great clinical significance. In this review, we summarize the literature on leukoaraiosis in recent years with the aim of elucidating the disease in terms of various aspects (including pathogenesis, imaging features, and clinical features, etc.).